A homozygous missense variant in type I keratin KRT25 causes autosomal recessive woolly hair. Issue 10 (9th July 2015) - Ansar, Muhammad; Raza, Syed Irfan; Lee, Kwanghyuk; Irfanullah,; Shahi, Shamim; Acharya, Anushree; Dai, Hang; Smith, Joshua D; Shendure, Jay; Bamshad, Michael J; Nickerson, Deborah A; Santos-Cortez, Regie Lyn P; et al.
Abstract : Background: Woolly hair (WH) is a hair abnormality that is primarily characterised by tightly curled hair with abnormal growth. Methods: In two unrelated consanguineous Pakistani families with non-syndromic autosomal recessive (AR) WH, homozygosity mapping and linkage analysis identified a locus within 17q21.1–q22, which contains the type I keratin gene cluster. A DNA sample from an affected individual from each family underwent exome sequencing. Results: A homozygous missense variant c.950T>C (p.(Leu317Pro)) within KRT25 segregated with ARWH in both families, and has a combined maximum two-point LOD score of 7.9 at ϴ=0. The KRT25 variant is predicted to result in disruption of the second α-helical rod domain and the entire protein structure, thus possibly interfering with heterodimerisation of K25 with type II keratins within the inner root sheath (IRS) of the hair follicle and the medulla of the hair shaft. Conclusions: Our findings implicate a novel gene involved in human hair abnormality, and are consistent with the curled, fragile hair found in mice with Krt25 mutations, and further support the role of IRS-specific type I keratins in hair follicle development and maintenance of hair texture.